2017
DOI: 10.1108/qaoa-05-2017-0015
|View full text |Cite
|
Sign up to set email alerts
|

Structural relationship between emotional and social support for young adult carers towards intergenerational care of the multi-ethnic elderly

Abstract: Purpose The purpose of this paper is to examine the structural relationship between the emotional and social support provided for individuals with caring responsibilities for elderly relatives, and the quality of care actually delivered. In addition, the moderating role of gender is explored. Design/methodology/approach A quantitative research design was utilised in which 200 usable questionnaires were collected from 250 respondents comprised of young adults who adopt a caregiving roles in respect of elderly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…In Malaysia, good social support was confirmed to have reduced carers' pressures. Nawi et al (2017) reported that positive social support facilitated young adult Malaysian carers to fulfill caring duties toward parents or close relatives.…”
Section: The Impact Of Social Support and Unresolved Research Issuesmentioning
confidence: 99%
“…In Malaysia, good social support was confirmed to have reduced carers' pressures. Nawi et al (2017) reported that positive social support facilitated young adult Malaysian carers to fulfill caring duties toward parents or close relatives.…”
Section: The Impact Of Social Support and Unresolved Research Issuesmentioning
confidence: 99%
“…Therefore, the sustainment of salubrious intergenerational relationships is necessary for caregiving, given that members of older generations become the primary responsibility of subsequent generations [55]. Intergenerational caregiving refers to caregiving activities that transpire between generations, which sometimes skip a generation [56].…”
Section: Introductionmentioning
confidence: 99%